On the Formation of Adiabatic Shear Bands in Textured HCP Polycrystals - Zhang,Z; Eakins,DE; Dunne,FPE (International Journal of Plasticity, 2015)
Adiabatic shear band (ASB) formation in textured HCP polycrystals has been investigatedunder regimes of high rate compression and shear loading using dynamic thermomechanicallycoupled, dislocation-based crystal plasticity modelling. The balance betweenrate of plastic dissipation leading to internal heat generation versus rate of thermal diffusionat a crystallographic length scale has been shown to be pivotal for the formation or otherwiseof ASBs. Micro-texture has been found to have a key role in both advancing and inhibitingshear band growth, and its control offers the possibility of new alloys with higher impactstrength over strain rate range 2 1 10 to 5 110 s-1. Texture has been found to lead to widevariations in applied macroscopic strain at which ASB formation occurs, such that strain levelin isolation is inappropriate as a universal indicator of ASB onset.High-rate shear loading is found to lead to lower onset strains for ASBs compared to highrate compression, but the dependence of both on texture leads to considerable variation instrain level for ASB formation. A preliminary map demarcating ASB onset has beenestablished over regimes of applied strain and texture for dynamic shear and compression.